Long Bone Fractures and Mineral-Bone Disorders in Patients with Chronic Kidney Disease Treated with Hemodialysis - Ankin, M.L.; Petryk, T.M.; Ladyka, V.O.; Dudar, S.L. (TERRA ORTHOPAEDICA, 2023)
Background. At the turn of the 20th and 21st centuries, the world community was faced with a global problem that has not only medical, but also great social economic significance – a pandemic of chronic non-communicable diseases that annually claim millions of lives, lead to severe complications associated with disability and the need for high-cost treatment. Among them is chronic kidney disease (CKD), which occupies an important place due to its significant prevalence in the population, a sharp decrease in the quality of life, high mortality of patients, and which leads to the need for expensive methods of renal replacement therapy (RRT). Objective: to determine the 3-year cumulative fracture rate (proportion of adults with fractures of the femur, forearm, or proximal part of the humerus) at least once during 3 years of follow-up, and the level of calcium, phosphorus, parathyroid hormone (PTH), alkaline phosphatase and vitamin D in patients who are treated with programmed hemodialysis and have long bone fractures. Materials and Methods: To determine the 3-year cumulative fracture rate (proportion of adults with fractures of the femur, forearm, or proximal part of the humerus) at least once during the 3-year follow-up, 512 patients treated with hemodialysis for more than 3 years were observed. 50 bone fractures were diagnosed during 2019-2022 (femur – 25, tibia – 6, proximal part of the humerus – 6, forearm – 4, pelvis – 2, ribs – 2, vertebrae – 5). Results. A more detailed study of indicators of mineral metabolism was conducted on 154 patients with CKD stage V who were treated with hemodialysis at the MNPE “Kyiv Regional Clinical Hospital” of the KCC. Subsequently, the patients were divided into 2 groups: (1) patients on hemodialysis with fractures of long bones of the skeleton (n=41: femur – 25, tibia – 6, proximal part of the humerus – 6, forearm – 4) who were treated at the regional trauma center, and (2) patients without skeletal fractures (n=118) in 2019- 2022. Conclusions. The study showed that the 3-year cumulative fracture rate in a study of 512 patients treated with hemodialysis for more than 3 years was 9.76%. Compared with patients without fractures, patients with fractures of long bones had increased levels of phosphorus and PTH and decreased levels of calcium and vitamin D in the blood serum. The level of alkaline phosphatase in the presence of fractures was twice as high as in the group of patients without fractures (p<0.001). The data indicate that disorders of mineral metabolism are the etiological factors of fractures in patients with CKD who are treated with hemodialysis.